Intellectus gratiae : die erkenntnistheoretische und hermeneutische Dimension der Gnadenlehre Augustins von Hippo - Lössl, Josef. (Vigiliae Christianae, Supplements, 1997)
This is the first large scale study on the link between the concepts of intellect and grace in the writings of St. Augustine of Hippo. Its five chapters deal with Augustine's writings on grace as they focus on questions concerning epistemology and hermeneutics. Already non-Christian ancient philosophers identified intellectual perfection with salvation as caused by divine grace. Under their influence (I) Augustine developed also his biblical thought (II). The culmination of his concept of intellectus gratiae , however, came in the later works on sacraments (III), hermeneutics (IV) and against Pelagius and Julian of Eclanum (V). This study highlights that development and recommends the concept of intellectus gratiae as a possible key to Augustine's theological thought as a whole.